2018
DOI: 10.1002/jhet.3417
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and QSAR Study of Some Novel Heterocyclic Derivatives as In Vitro Cytotoxic Agents

Abstract: 2,3‐Diaryloxirane‐2,3‐dicarbonitriles have employed in heterocyclic synthesis in many organic reactions. Authors highlight its use as intermediate in the synthesis of various organic compounds through the reaction with different nitrogen nucleophiles as methyl hydrazine, thiourea, thiosemicarbazide, methylglycinate, and others to furnish new heterocyclic derivatives. They are also used as key starting materials to construct some important heterocycles. Structures of all newly synthesized products are substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…DFT indicated the proposal mechanism of the phthalazine-1-ol via ring-opening of benzylidene phthalide ( 1 ) using hydrazine hydrate followed by 4-chlorobenzaldehyde ( 2 ) to afford the hydrazide ( 3 ) that is confirmed thermodynamic parameters the electrophilicity of the benzylidene phthalide was more than 4-chlorobenzaldehyde ( Figure 9 ). Therefore, we can support the experimental suggestion [ 29 ] that the second singlet excited state of phthalazine is an np∗ state with a small oscillator strength. Finally, we can give also a good reason for the higher activity of phthalazin-1-ol in the cytotoxicity of anticancer due to this reaction is include the reactive speeches of OH group.…”
Section: Dft-characterization Based On the Thermodynamic Aspectssupporting
confidence: 89%
See 1 more Smart Citation
“…DFT indicated the proposal mechanism of the phthalazine-1-ol via ring-opening of benzylidene phthalide ( 1 ) using hydrazine hydrate followed by 4-chlorobenzaldehyde ( 2 ) to afford the hydrazide ( 3 ) that is confirmed thermodynamic parameters the electrophilicity of the benzylidene phthalide was more than 4-chlorobenzaldehyde ( Figure 9 ). Therefore, we can support the experimental suggestion [ 29 ] that the second singlet excited state of phthalazine is an np∗ state with a small oscillator strength. Finally, we can give also a good reason for the higher activity of phthalazin-1-ol in the cytotoxicity of anticancer due to this reaction is include the reactive speeches of OH group.…”
Section: Dft-characterization Based On the Thermodynamic Aspectssupporting
confidence: 89%
“…In the macroscopic non-isothermal state, if an arbitrary material ensemble dissolved thermally, then the mass conversion fraction of degradable ensemble could be described in what follows [ 29 , 30 , 31 , 32 ]. Where, E(T) is dimensionless function can be calculated as: Where, χ_i is the mass conversion fraction, 1-χ_iis the residual mass, λ = β∖/A and ρ = Ei ∖/R, R is the gas constant.…”
Section: Macroscopic Study Using Theoretical Arrhenius Modelmentioning
confidence: 99%
“…Control ( HepG-2 cells without treatment). It was previously reported that the thermal and microwave re ux of chalcone 1 with diversity of active methylene for instance ethyl cyanoacetate, ethyl acetoacetate and diethyl malonate with ammonium acetate produced the pyridine esters 2a-c and 2-pyridone derivatives 3a-c in good yield that outlined in Scheme 1 [43][44][45][46][47][48].…”
Section: Quanti Cation Of P21 and Caspase-3 Gene Expression And Oxidatimentioning
confidence: 99%
“…Quinazolinones and quinazolines are noteworthy in medicinal chemistry [1,2], quinazolinone nucleus stability pushed a lot of researchers to introduce many bioactive moieties to this nucleus to produce new potential medicinal agents [3]. From a literature survey, the quinazolin-4 (3H)-one derivatives are of interest because of their wide biological activities [4][5][6][7][8][9][10][11][12][13] carrying antimicrobial sites as considered a wide array of pharmaceutical properties [14][15][16][17][18][19][20][21][22][23]. Moreover, quinazolinones are considered the most important component of most natural alkaloids in some families of plants, animal, and microorganisms [24].…”
Section: Introductionmentioning
confidence: 99%